Six-Color Confocal Immunofluorescence Microscopy with 4-Laser Lines - Heger, Lukas; Lühr, Jennifer J.; Amon, Lukas; Smith, Ana-Suncana; Eissing, Nathalie; Dudziak, Diana (Methods in Molecular Biology, 2021)
Confocal immunofluorescence microscopy is an advanced imaging technique routinely applied in the laboratory and clinics. Histological analyses are performed from tissue material. In general, a single fluorochrome per laser is employed, limiting simultaneous analysis to four antigens in one staining with a conventional 4-laser line microscope. Here, we describe a protocol for combining fluorochromes with the same excitation but different emission properties that allows for the analysis of six different antigens in confocal immunofluorescence microscopy with a conventional 4-laser line microscope. The proposed multiplexed method permits the identification and characterization of complex cell populations in rare tissue material.
CRIS-Team Scopus Importer:2021-10-01
Keywords: DC; Dendritic cells; Fluorochrome; Histology; Multicolor imaging; Tissue